Resistance and conservation in the Maestrazgo-Els Ports initiative: The complexities behind failed conservation - Ponzi, Brenda Sofía (2025)
At the end of 2019, the Maestrazgo-Els Ports initiative was presented publicly with the aim of creating an international ecotourism destination of 550,000 hectares located between the provinces of Castellón, Teruel, and Tarragona, Spain. In less than seven months, the proposal was withdrawn due to the high level of conflict it unleashed. Resistance to the project was led by different agents who defended cultural and linguistic diversity, traditional productive activities, and the production of wind energy in the region. In a context of confinement due to the COVID-19 pandemic, detractors used social networks and the press as tools to nullify it completely. The dispute was redefined as a territorial defense against top-down projects, a criticism of urban-centrism and a commitment to autonomy by local groups. The result of this confrontation meant the end of an initiative that sought to combine nature and local development through tourism in an area characterized by high rates of depopulation and a shortage of socioeconomic alternatives, but it also opened the doors to the consolidation of wind extractivism in the zone. This case study provides a detailed example of the socioeconomic tensions that permeate the implementation of a land conservation program. This article focuses on the analysis of the concept of resistance, avoiding a single simplified definition and focusing instead on the multiple dimensions of any process of opposition to an initiative of this type.